The readiness of mathematics teachers in south sumatra province to conduct online learning from the TPACK perspective - Heru, Heru; Yuliani, Refi Elfira; Septra Nery, Rieno (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2023)
Information and Communication Technology (ICT) use in digital-era learning leads to online learning. Implementing online learning requires a combination of skills from teachers in integrating pedagogical knowledge, subject matter mastery, and technological skills to create effective learning. This study aims to investigate the readiness of Mathematics teachers in the South Sumatra Province to conduct online learning from the TPACK perspective. This research is a survey type of study. The research subjects are Mathematics teachers in South Sumatra who teach Mathematics subjects at the primary, secondary, and high school levels. The sample used in this study amounted to 170 people. Based on the results discussed, Mathematics teachers in the South Sumatra Province are ready to conduct online learning based on the TPACK perspective. The highest readiness component for conducting learning is Technological Knowledge (TK), and the lowest is Technological Pedagogical and Knowledge (TPACK).